Grupy rówieśnicze (peer groups) a decyzje migracyjne = Peer groups and migration decisions - Pustułka, Paula; Sarnowska, Justyna; Grabowska, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to develop a typology of peer groups (groups of friends) from selected local communities and to show the influence such groups may exercise on spatial mobility (internal and international migrations). Respondents aged 19-34 retrospectively outlined high-school groups made up of both migrants and non-migrants. The article is based on the first round of a qualitative longitudinal study carried out in many places.
Keywords: grupa rówieśnicza; społeczności lokalne; migracja; peer group; local communities; migrations